A christmas legacy eaudiobook - Perry, Anne (Christmas Stories, 2021)
Thomas and Charlotte Pitt's former maid takes a new job as Christmas approaches—but not everyone in the household may survive the holidays in this tension-filled novel from bestselling author Anne Perry. After leaving her position with Charlotte and Thomas Pitt to get married, Gracie thought her days as a maid were behind her. But when Millie, the daughter of a long-gone friend, turns up on Gracie's doorstep just before the holidays, frantic because things are going missing from the kitchen in the household she serves, Gracie knows that she must find out what's happening. Millie can't risk being accused of theft and getting thrown out on the street without character references. So Gracie takes on Millie's job herself, claiming that Millie is sick and needs a few days to recuperate. At first, it seems that all is normal in the household, even if her temporary employer's elderly grandmother keeps entirely to her bedroom upstairs. But Gracie soon realizes that Granny is suffering from neglect—and rather than helping her, the husband and wife have decided she isn't dying fast enough. Can Gracie thwart their plans in time to save the old woman's life?